The morpho-physiological effect of drought and drought QTL analysis on Bambara Groundnut (Vigna Subterranean (L) Verdc) - Krishnamoorthy, Mahaletchumy (2020)
Global warming threatens global food production with rising temperatures and increasing periods of drought. Bambara groundnut with its relatively high percentage of seed protein and its ability to produce some yield where other crops fail seems to fit the characteristics of an alternative crop for the future. Although Bambara groundnut is said to be drought tolerant and is more resilient than many other crops, few studies have been carried out on this crop in comparison to other crops, especially in terms of drought tolerance. The aim of the study is to evaluate the different genotypes and a segregating population under drought and perform QTL analysis of agronomic and drought related traits for the mapped populations.